On the gold-catalyzed generation of phenyl cations from 1,5-Diynes - Wurm, Thomas; Bucher, Janina; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Advanced synthesis & catalysis, 2017)
cis-Enediyne systems bearing two non-terminal alkyne functionalities were transformed in the presence of a gold catalyst. A selective 6-endo-dig-cyclization generates mono-aurated phenyl cation intermediates, high energy species that are able to activate even primary sp3-C-H-bonds. Via insertion into intramolecularly offered, unactivated C-H-bonds, penta-substituted benzene derivatives are obtained as final products. In most cases selective insertions into the γ-sp3-C—H bonds of the offered tethers were observed.
Gesehen am 28.08.2017